2015
DOI: 10.1152/ajpheart.00621.2014
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of vascular dysfunction and arterial hypertension in mice generated by assisted reproductive technologies by addition of melatonin to culture media

Abstract: Rexhaj E, Pireva A, Paoloni-Giacobino A, Allemann Y, Cerny D, Dessen P, Sartori C, Scherrer U, Rimoldi SF. Prevention of vascular dysfunction and arterial hypertension in mice generated by assisted reproductive technologies by addition of melatonin to culture media. Am J Physiol Heart Circ Physiol 309: H1151-H1156, 2015. First published August 14, 2015; doi:10.1152/ajpheart.00621.2014.-Assisted reproductive technologies (ART) induce vascular dysfunction in humans and mice. In mice, ART-induced vascular dysfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 36 publications
1
42
0
1
Order By: Relevance
“…In a subsequent study, the authors demonstrated that the addition of melatonin in the culture media prevented artery vasodilation, arterial blood pressure, and associated Nos3 promoter methylation effects in IVF mice [54]. While the exact mechanism of melatonin rescue has yet to be elucidated, importantly, this work highlights the importance of embryo culture conditions in the prevention of adverse effects.…”
Section: Evidence That Art Can Increase the Risk Of Cardiometabolimentioning
confidence: 88%
“…In a subsequent study, the authors demonstrated that the addition of melatonin in the culture media prevented artery vasodilation, arterial blood pressure, and associated Nos3 promoter methylation effects in IVF mice [54]. While the exact mechanism of melatonin rescue has yet to be elucidated, importantly, this work highlights the importance of embryo culture conditions in the prevention of adverse effects.…”
Section: Evidence That Art Can Increase the Risk Of Cardiometabolimentioning
confidence: 88%
“…We speculated that addition of melatonin to the culture media may have favourable eff ects on the cardiovascular phenotype in ART mice. We found that addition of melatonin normalized the methylation pattern in the preimplantation embryo and prevented the altered methylation, expression and function of the eNOS gene in vascular tissue and, in turn, prevented mesenteric artery endothelial dysfunction and arterial hypertension in adult ART mice [73] (Figure 7).…”
Section: Role Of Epigenetic Mechanisms In Art-induced Alteration Of Tmentioning
confidence: 88%
“…On the other hand, ART can induce vascular dysfunction and arterial hypertension related to epigenetic alterations of the regulation of the eNOS gene; however this can be prevented by addition of melatonin during in vitro culture of embryos which doubled the success rate of IVF, prevented eNOS demethylation and normalized NO plasma concentration [131].…”
Section: Potential Use Of Melatonin Against Nitrosative Stress Duringmentioning
confidence: 99%